2023
DOI: 10.21203/rs.3.rs-2416773/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decision makers find it difficult to compare and select similar systematic reviews based on quality, methods and results: a cross-sectional survey

Abstract: Background Systematic reviews (SRs) are being published at an accelerated rate. Decision makers are often faced with the challenge of comparing and choosing between multiple SRs on the same topic. We surveyed individuals in the healthcare field to understand what criteria they use to compare and select one or more SRs from multiple on the same topic. Methods We developed a survey with 21 open and closed questions. We disseminated it through social media and professional networks. Results Of the 684 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…AMSTAR 2 could be used to detect SRs with the lowest confidence ratings and exclude them from the pool of relevant SRs for policy development or health decision-making [39]. Such classification of SRs could be helpful for decision makers, who find it difficult to select appropriate SRs for their work [40]. Our recommendations could be considered to improve the usability of AMSTAR 2 for health decision-making.…”
Section: Implications For Practicementioning
confidence: 99%
“…AMSTAR 2 could be used to detect SRs with the lowest confidence ratings and exclude them from the pool of relevant SRs for policy development or health decision-making [39]. Such classification of SRs could be helpful for decision makers, who find it difficult to select appropriate SRs for their work [40]. Our recommendations could be considered to improve the usability of AMSTAR 2 for health decision-making.…”
Section: Implications For Practicementioning
confidence: 99%
“…The appraisals with these two items could be performed by less experienced users of AMSTAR 2 because presence of a review protocol and a list of excluded studies can be identified relatively fast and does not require as much methodological expertise as some other items on AMSTAR 2 (e.g., item 11 that requires a judgement of methods used in a meta-analysis). Since decision makers find it difficult to select appropriate SRs for their work [ 14 ], the appraisal approach with two critical items could assist with SR classification and selection for further work. For example, such an approach can be used when large numbers of SRs on a similar topic are available for their potential application in health decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…912 We have recently conducted a survey confirming that more than 50% of decision-makers have difficulty choosing the best evidence on a given topic: the methodological quality, the reputation of the authors and the journal, and the type of primary studies included were among the features thought to be important by respondents. 13…”
Section: Introductionmentioning
confidence: 99%